2015
DOI: 10.5194/acp-15-8809-2015
|View full text |Cite
|
Sign up to set email alerts
|

The anthropogenic contribution to atmospheric black carbon concentrations in southern Africa: a WRF-Chem modeling study

Abstract: Abstract. South Africa has one of the largest industrialized economies in Africa. Emissions of air pollutants are particularly high in the Johannesburg-Pretoria metropolitan area, the Mpumalanga Highveld and the Vaal Triangle, resulting in local air pollution. This study presents and evaluates a setup for conducting modeling experiments over southern Africa with the Weather Research and Forecasting model including chemistry and aerosols (WRF-Chem), and analyzes the contribution of anthropogenic emissions to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…The temperature biases found at stations in the present study are in the same range as the ones found in other regions with WRF (Zhang et al, 2013(Zhang et al, , 2016Mar et al, 2016;Kuik et al, 2015), particularly when considering that the reported 2m 10 temperature biases in these studies tend to be higher in mountainous terrain than in other regions. For example, Zhang et al …”
supporting
confidence: 74%
See 1 more Smart Citation
“…The temperature biases found at stations in the present study are in the same range as the ones found in other regions with WRF (Zhang et al, 2013(Zhang et al, , 2016Mar et al, 2016;Kuik et al, 2015), particularly when considering that the reported 2m 10 temperature biases in these studies tend to be higher in mountainous terrain than in other regions. For example, Zhang et al …”
supporting
confidence: 74%
“…They also found that the spatiotemporal variability of precipitation is reproduced reasonably well in this region but with an overestimation of precipitation in summer and an underestimation during other seasons. In the literature reviewed for this study, black carbon concentrations 5 are consistently underestimated by the WRF-Chem model, independent of the region (e.g., Europe (Tuccella et al, 2012), East Asia (Zhang et al, 2016) and South Africa (Kuik et al, 2015)). …”
Section: Introductionmentioning
confidence: 99%
“…In this context, atmospheric models with an explicit treatment of the physical and chemical processes become an indispensable tool to the studies of the urban pollution impact. Several numerical studies can be found with special focus on different aspects of the pollution impact, such as pollution episodes Michael et al, 2013;Kuik et al, 2015), regional and longdistance transport (Tie et al, 2007;Guo et al, 2009;Lin et al, 2010), secondary formation of gases and particles (Yerramile et al, 2010;Jiang et al, 2012;Lowe et al, 2015), and the effects of land use and land cover changes (Capucim et al, 2015;Rafee et al, 2015). However, such studies did not investigate the impact of isolated urban plumes.…”
Section: S a Abou Rafee Et Al: Contributions Of Mobile Stationarymentioning
confidence: 99%
“…assuming aerosol properties and the use of global instead of regional emission inventories for under-sampled/characterised regions). Considering the relatively short atmospheric lifetime of BC, such assumptions could lead to significant uncertainties, especially on regional scales (Andreae and GelencsĂ©r, 2006;Masiello, 2004;Bond et al, 2013;Kuik et al, 2015). For a better understanding of the transport, removal and climatic impacts of atmospheric BC, accurate and up-to-date measurements covering large spatial areas and long temporal periods are required.…”
Section: Introductionmentioning
confidence: 99%
“…Maritz et al (2015) and Aurela et al (2016) presented limited EC mass concentration data from some regional background sites in South Africa. Kuik et al (2015) used the Weather Research and Forecasting model, including chemistry and aerosols (WRF-Chem), to analyse the contribution of anthropogenic emissions to the total tropospheric BC mass concentrations from September to December 2010 in South Africa. However, significant underestimations and uncertainties with regard to BC mass concentrations were reported by the aforementioned authors.…”
Section: Introductionmentioning
confidence: 99%